"Well, You Can't Force Them": Altercasting in the Home Health Care Context. Issue 1 (1st January 2019) - Kendall, Peggy S.; Scott, Muriel; Jolivette, Krista
Abstract : Home health aides are often low-paid, low-status workers, performing their job in an isolated and interpersonally complex environment. This study, made up of semistructured interviews with 36 home health aides, explores compliance-gaining challenges faced by "low status, remote workers." It was found that altercasting, a compliance-gaining technique using social roles to govern behavior, is well suited for the home care context. Aides were found to activate four altercast roles, including parent, trainer, employee, and friend. It is suggested that by using positive altercasting as a compliance-gaining technique, aides are able to both persuade their client to complete necessary tasks of daily living at the same time they construct and maintain the moral identity of a good caregiver.